Edukasi Pemilahan dan Pemanfaatan Sampah Organik dan Non Organik di Desa Tembesi, Batam - Sumantika, Arsyad; Sirait, Ganda; Prasetyo, Bahariandi Aji; Oktavia, Yunisa (Jurnal Pengabdian Cendikia Nusantara, 2024)
Waste is a serious problem that is often encountered in today's society. This community service activity was carried out in Tembesi Village, Batam Regency. The knowledge and practices of waste management in the Tembesi Village community are still limited. Inadequate supporting facilities also worsen this situation. Therefore, it is important to increase public awareness so that they don't just throw away rubbish, but also educate them on how to sort waste. Based on these problems, this community service activity aims to provide a solution through education on the importance of maintaining cleanliness, sorting and separating organic and inorganic waste and utilizing waste that has been processed in such a way that it has economic value. The actual form of this activity is to support the provision of separate waste bin facilities. The method used in carrying out this service activity is education. Through this service activity, the community becomes aware of the importance of maintaining cleanliness, understands better how to sort waste independently and better understands the benefits. Apart from that, Tembesi residents can also feel the benefits of processing waste using the 3R method, namely Reduce, Reuse, Recycle.